Pharmacokinetics, Food Effect, Ketoconazole Interaction, and Safety of JTK‐853, a Novel Nonnucleoside HCV Polymerase Inhibitor, After Ascending Single and Multiple Doses in Healthy Subjects. Issue 3 (19th February 2019) - Tamaki, Sekihiro; Shibata, Tsutomu; Hunt, Thomas; Gerhardt, Barbara; Yamada, Hiroyuki; Pai, Sudhakar M.
Abstract: Pharmacokinetics, safety, and tolerability of JTK‐853, a novel HCV polymerase inhibitor, were evaluated in single and multiple ascending dose (SAD, MAD) studies, with food‐ and ketoconazole‐related effects on exposure to JTK‐853 and its active (CYP3A4 mediated) metabolite M2. JTK‐853 was safe and well tolerated in both studies. In the SAD study, at doses >1600 mg (with standard breakfast [SBF]), JTK‐853 exposure did not increase further, was substantially higher (AUCinf increase: 3‐ to 8‐fold) with SBF (vs fasted), with a moderate increase in AUCinf (approximately 1.5‐fold [1600 mg]) with a high‐fat breakfast (vs SBF). In the SAD study (400–1600 mg, SBF), mean effective half‐life (t1/2(eff) ) of JTK‐853 was 8.3 to 10.9 hours, and 20.3 to 27.3 hours in the MAD study (twice daily dosing, fed condition), with 2‐ to 3‐fold accumulation in exposure (AUCtau ). At steady‐state, AUCtau increased dose proportionally, and was approximately 2‐fold higher with ketoconazole coadministration. Metabolite M2 (equipotent to JTK‐853 in vitro) did not contribute significantly to parent drug exposure and decreased with increase in dose, repeated dosing, and ketoconazole coadministration. Trial simulation‐based ratios (n = 1000/dose level) of trough JTK‐853 plasma concentrations to the in vitro EC90 for HCV genotype 1b were assessed for dose selection in a separate proof‐of‐concept study in patients. The studies enabled delineation of key drug attributes for further assessments in the target population.